Post-Exercise Rehydration: Effect of Consumption of Beer with Varying Alcohol Content on Fluid Balance after Mild Dehydration - Wijnen, Annemarthe H. C.; Steennis, Jora; Catoire, Milène; Wardenaar, Floris C.; Mensink, Marco (Frontiers in Nutrition, 2016)
Purpose: The effects of moderate beer consumption after physical activity on rehydration and fluid balance are not completely clear. Therefore, in this study we investigated the effect of beer consumption, with varying alcohol content, on fluid balance after exercise-induced dehydration. Methods: Eleven healthy males were included in this cross over study (age 24.5 ± 4.7 yrs, body weight 75.4 ± 3.3 kg, VO2max 58.3 ± 6.4 mL · kg · min-1). Subjects exercised on a cycle ergometer for 45 min at 60 % of their maximal power output (Wmax) until mild dehydration (1 % body mass loss). Thereafter, in random order, one of five experimental beverages was consumed, in an amount equal to 100% of their sweat loss: non-alcoholic beer (0.0 %), low-alcohol beer (2.0 %), full-strength beer (5.0 %), an isotonic sports drink and water. Fluid balance was assessed up till 5 hours after rehydration. Results: After 1 hour, urine production was significantly higher for 5 % beer compared to the isotonic sports drink (299 ± 143 mL vs 105 ± 67 mL; p < 0.01). At the end of the 5 h observation period net fluid balance (NFB) was negative for all conditions (p = 0.681), with the poorest fluid retention percentage for 5 % beer (21 % fluid retention) and the best percentage for the isotonic sports drink (42 %). Non-alcoholic beer, low-alcoholic beer and water resulted in fluid retention of 36 %, 36 % and 34 % respectively (p = 0.460). Conclusions: There was no difference in NFB between the different beverages. Only a short-lived difference between full-strength beer and the isotonic sports drink in urine output and NFB was observed after mild exercise-induced dehydration. Fluid replacement – either in the form of non-alcoholic beer, low-alcoholic beer, full-strength beer, water or an isotonic sports drink of 100 % of body mass loss was not sufficient to achieve full rehydration. The combination of a moderate amount of beer, with varying alcohol content, enough water or electrolyte- and carbohydrate beverages, and salty foods might improve rehydration, but more research is needed.